MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR GEOGRAFI PADA MATERI LINGKUNGAN HIDUP DENGAN MENGGUNAKAN PEMBELAJARAN BERBASIS MASALAH DI KELAS XI IPS 1 SMAN 1 KANDANGAN TAHUN AJARAN 2013/2014 - Nanang Nurudin (Universitas Lambung Mangkurat, 2014)
The preliminary observation on the students learning activities and learning outcomes in Geography subject in Grade XI Social Study 1 SMAN 1 Kandangan shows that the learning outomes are still low, so that teacher innovation is needed in using learning models to improve their students learning activities and their learning outcomes in Geography with environment as the topic by implementing problem- based learning model. This is a classroom action research consisting of two cycles. It is conducted at SMAN 1 Kandangan. The subjects are 29 students of grade XI Social Study 1 (XI IPS 1) SMAN 1 Kandangan in the Academic Year 2013/2014. The result of the research shows that the students’ learning activities in grade XI Social Study 1 of SMAN 1 Kandangan have improved in the first cycle. The students learning activities are at active category 29.1 % and very active 6.1%. In the second cycle, the students’ learning activities are at active category 50.6 % and very active 48.7 %. The learning outcomes in the first cycle show that post-test average score reaches 75.86% and classical completeness 75.86%. In the second cycle, the post-test average score reaches 80.3% and the classical completeness 100%. Positive responses are shown by the students in using problem-based learning.Keywords: learning activities, problem-based learning model, learning outcomes of geography